Toward a Theology of Acts: Reading and Rereading - Gaventa, Beverly Roberts (Interpretation, 1988)
To see in Acts only the triumphalist theology of a God who overruns all opposition is to miss the equally strong emphasis in this narrative on the rejection of the gospel and the persecution of its apostles; both are needed if Acts' theology is to be correctly understood.